Post‐marketing research and its outcome for novel anticancer agents approved by both the FDA and EMA between 2005 and 2010: A cross‐sectional study. Issue 2 (12th October 2017) - Zeitoun, Jean‐David; Baron, Gabriel; Vivot, Alexandre; Atal, Ignacio; Downing, Nicholas S; Ross, Joseph S; Ravaud, Philippe
Abstract : Post‐marketing research in oncology has rarely been described. We aimed to characterize post‐marketing trials for a consistent set of anticancer agents over a long period. We performed a cross‐sectional analysis of post‐marketing trials registered atClinicalTrials.gov through September 2014 for novel anticancer agents approved by both the US Food and Drug Administration and the European Medicines Agency between 2005 and 2010. All relevant post‐marketing trials were classified according to indication, primary outcome, starting date, sponsors, and planned enrollment. Supplemental indications were retrieved from regulatory documents and publication rate was assessed by two different methods. Ten novel anticancer agents were eligible: five were indicated for hematologic malignancies and the remaining five for solid cancers (three for kidney cancer). We identified 2, 345 post‐marketing trials; 1, 362 (58.1%) targeted an indication other than the originally approved one. We observed extreme variations among drugs in both number of post‐marketing trials (range 8–530) and overall population to be enrolled per trial (1–8, 381). Post‐marketing trials assessed almost all types of cancers, the three most frequently studied cancers being leukemia, kidney cancer and myeloma. In all, 6.6% of post‐marketing trials had a clinical endpoint as a primary outcome, and 35.9% and 54.1% had a safety or surrogate endpoint, respectively, as a primary outcome. Nine drugs obtained approval for supplemental indications. The publication rate at 10 years was 12.3 to 26.1% depending on the analysis method. In conclusion, we found that post‐marketing research in oncology is highly heterogeneous and the publication rate of launched trials is low. Abstract : What's new? In contrast to clinical research preceding drug approval, post‐marketing research is much less regulated and has rarely been described. This study characterized nearly 10 years of post‐marketing research for all novel anticancer agents approved by the Food and Drug Administration and European Medicines Agency between 2005 and 2010. There was a high degree of heterogeneity in the number of trials and size of population to be enrolled. 60% of post‐marketing trials were designed for a new indication, most commonly hematologic and kidney cancers. Very few trials had a clinical endpoint as a primary outcome, and publication rate was particularly low.